Uma série de contos e os contos em série : o imaginário pós-moderno em Once Upon a Time - Azubel, Larissa Lauffer Reinhardt (2017)
This research seeks to comprehend the manifestation of the postmodern imaginary in the feeric serial narrative Once Upon a Time. Moved by this purpose, it goes through a path in which plots and characters suffer metamorphoses, to understand how the spirit of time shows itself up in the first season of this series. The key notions that guide it are of imaginary (and its technologies) and of postmodernity. But it also counts on the theoretical contribution of the fairy tales and of the television series. Through them, the Comprehensive Sociology, as method, and the Comprehensive Film Analysis of Serialized Narrative, as research technique, it launches into the cartography of Once Upon a Time in the field of Sociology Communication. With this theoretical and methodological basis, it deciphers the living imaginary micromuseum of this series, which reveals itself as a metaphor (if not, a caricature) of contemporary sociality. In addition, in the anthropological path of this research, it is proposed, among other theoretical advances, its own notions of imaginary, regime of contemporary images, postmodernity, communication and fairy tales. It is also suggested a new way of analyzing television series.